Tourism And Conflict : The Empirical Study Of Sipin Lake Development, Jambi City - M. Yusuf; Faizah Bafadhal; Maratun Saadah (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
The purpose of this paper is to analyze the causes of conflict and propose alternative conflict resolution in tourism development. Although this sector experienced a significant growth and was able to encourage economic growth at various levels, its management faces governance challenges for instance conflicts of interest that occur in the Sipin lake area. This area constructed in 2017 which is designated as a tourist area based on regional regulations spatial plan of Jambi city. The data is obtained from various field information through in-depth interviews, observations and various sources which then it is systematically coded to find the meaning behind the phenomena that occur. This paper reveals that conflict in development of tourism objects is triggered by the planning and implementing non-participatory regional development and differences in orientation among the actors involved. The management of an area of ± 161 ha is not maximum managed, and this can be seen from the management of the area that is not well-organized and untidy. This paper underlines that tourism conflicts can occur due to various things that result in poor tourism management so that the potential to reduce the number of visitors.